COVID-19’s impact and telehealth practice in chronic pain management services: a nationwide study - Jantarada, Cláudia (2021)
Introduction: COVID-19 brought restrictions across chronic pain management services (CPMS), whose consequences should be objectified. Telehealth is being recommended in CPMS, however, the extent of its practice is unknown. We aimed to assess COVID-19’s impact and telehealth practice in Portuguese CPMS. Material and Methods: A cross-sectional survey was conducted in May 2020. CPMS’s description, telehealth practice, COVID-19’s impact in CPMS’s activity and opinions about telehealth practice were questioned to all Portuguese CPMS’s directors. We used descriptive statistics and chi-squared test was performed. A p-value<0.05 was considered significant for all tests. Results: The response rate was 59%.  Although there are regional and unit’s typology differences, COVID-19 brought an increase and a sophistication in telehealth practice, that is expected to be maintained in the future. COVID-19 led to major reductions of in-person consultations and procedures, increased patient-CPMS communication, and a non-negligible proportion of CPMS with an alarming wait time for first chronic pain consultations. Prediction of patient’s refusal/fear to attend CPMS, positive opinions about telehealth practice, previous telehealth practice and wait time for first consultation in chronic non cancer pain < 12 week, are associated with future telehealth practice. Discussion and Conclusion: Opinions about telehealth practice in CPMS were essentially positive and support future telehealth practice. This is the first nationwide study that objectifies the impact of COVID-19 and assesses telehealth practice in CPMS’s activity. This study may help health professionals and authorities improving telehealth practice and CPMS’s activity.